Relationship Between Physical Performance and Strength of the Ankle Muscles, Pain, and Kinesiophobia in Taekwondo Athletes With Chronic Ankle Instability - Beom-jun Kim; Ui-jae Hwang; Oh-yun Kwon (Physical Therapy Korea)
Background: Chronic ankle instability (CAI) is a prevalent condition among Taekwondo athletes, often associated with pain, psychological factors, and impaired physical performance. However, few studies have investigated the relationship among ankle muscle strength, pain, kinesiophobia, and physical performance in Taekwondo athletes with CAI. Objects: This study aimed to examine the relationship between ankle muscle strength, pain, kinesiophobia, and physical performance in Taekwondo athletes with CAI. Methods: Forty Taekwondo athletes with CAI participated in the study. Pain was assessed using the Visual Analogue Scale (VAS), and kinesiophobia was measured with the Tampa Scale for Kinesiophobia-11 (TSK-11). Physical performance was evaluated using the single-leg vertical jump (SLVJ) and single-leg hop for distance. The strength of the ankle muscles is measured using a Smart KEMA strength sensor. Pearson’s correlation coefficients were calculated to determine relationships among variables. Results: SLVJ showed a significant negative correlation with VAS (r = –0.506, p < 0.01) and a positive correlation with strength of the ankle inversion with dorsiflexion (IDF) (r = 0.356, p < 0.05). VAS was negatively correlated with strength of the ankle eversion with plantarflexion (r = –0.365, p < 0.05), IDF (r = –0.371, p < 0.05) and inversion with plantarflexion (r = –0.370, p < 0.05). No significant correlations were found between TSK-11 and physical performance, pain, or ankle muscle strength outcomes. Conclusion: Pain intensity and ankle muscle strength in specific ankle positions are associated with SLVJ in Taekwondo athletes with CAI. These findings suggest that the intensity of pain and the strength of the ankle evertor and invertor at specific ankle joint positions should be considered when evaluating Taekwondo athletes with CAI. Furthermore, managing pain and implementing strengthening exercises for the ankle evertor and invertor can be recommended to improve SLVJ.